Opacity - minority - improvisation : an exploration of the closet through queer slangs and postcolonial theory - T., Anna (Queer studies ;, 2020)
The expression »to come out of the closet« calls for an analysis of how language and notional as well as social spaces interact and intersect to constitute »queer«. This performative book, a product of artistic research, is an exploration of the proverbial closet through linguistics, queer, and post-colonial theory. It is a project in which opacity, minority, and improvisation happen on the levels of content, analysis, and typography. 11 queer slangs from around the world become part of an exploration of queerness and knowledge from the Periphery through autoethnography, Édouard Glissant's concept of opacity, José Muñoz's disidentifications, and Gloria Anzaldúa's performative writing. Theory, personal accounts, and art are interwoven to offer an interdisciplinary reading of the slangs as queer methods of survival and resistance.